IMPACT OF AGROFORESTRY TECHNOLOGIES ADOPTION AMONG RURAL FARMERS IN KADUNA STATE, NIGERIA - Sirajo, A.; Garba, M.; Idi, S.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the determinants of agroforestry technologies’ adoption among rural farmers in Kaduna State, Nigeria. Multi-stage sampling technique was used to select 400 respondents. Structured questionnaires were used for data collection and analysed using descriptive and inferential statics. The results revealed that windbreak (95.9%), alley cropping (94.2%), and live fencing (93.3%) were the most widely recognized agroforestry technologies among the respondents and were ranked 1st, 2nd, and 3rd, respectively. Meanwhile, alley cropping (96.1%) is the most widely adopted agroforestry technology among respondents, followed by live fencing (86.2%) and silvo-pasture (85.9%). The perception of respondents toward agroforestry technologies varied, as indicated by the mean values in Table 4. The findings showed that agroforestry helps in preventing soil erosion and land degradation (Mean = 4.40), silvopasture (Mean = 4.32), agroforestry increases farm productivity and provides an additional source of income (Mean = 4.06), and windbreaks and shelterbelts reduce wind speed and protect crops from damage (Mean = 4.13) were highly perceived by farmers. The result of t-test analysis revealed that there was a significant (P<0.01) difference between incomes before and after adoption of agroforestry technologies. Inadequate capital (98.15%), insecurity (97.24%), and climate change (96.13%) were the major constraints to agroforestry technology adoption in the study area and were ranked 1st, 2nd, and 3rd, respectively. The study concluded that there is significant improvement in farmers’ income following the adoption of agroforestry technologies since the average annual income of those after agroforestry technologies adoption is greater than those before adoption of agroforestry technologies. The study recommended that government and financial institutions should provide low-interest credit facilities strengthened farmers cooperatives to ease financial burdens on farmers and enjoys economy of scale. Local security agencies should strengthen rural security through community policing strategies to protect farmers and their investments.